Evaluasi Tingkat Keamanan Informasi pada Dinas Komunikasi dan Informatika Kabupaten Mojokerto dengan Menggunakan Indeks KAMI - Yusriyah Rahmah; Widhy Hayuhardhika Nugraha Putra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Dinas Komunikasi dan Informatika Kabupaten Mojokerto is a government agency that implements the development of information technology, but in the case of monitoring illegal access rights no record or documentation has been made. It is only handled when there has been a breakdown in the system, they have to pay concern about the safety of government information. In this research we try to measure information security management at Dinas Komunikasi dan Informatika Kabupaten Mojokerto using KAMI Index version 3.1 according to the standard of ISO / IEC 27001:2013. The evaluation result of information security completeness level is 109 and maturity level of each area of information security at the level I to level I +. It shows that information security at Dinas Komunikasi dan Informatika Kabupaten Mojokerto need to be improved. There are thirteen recommendations in the areas of information security governance, eight recommendations on the area of information security risk management, fifteen recommendations on areas of information security management framework, twenty four recommendations on the asset management area information, and the fourteen recommendations in the area of technology and information security. One of the recommendations for improvements by create organizational policies and procedures regarding information security using ITIL framework version 4 IT asset management practices.